Methodology For Developing Practical-Analytical Skills In Future Mathematics Teachers Through Mathematical Modeling Of Economic Processes - Ravshanova, Sadabgul Azamatovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article discusses the methodology for developing the practical and analytical skills of future mathematics teachers through modern mechanisms of interdisciplinary integration, specifically the mathematical modeling of economic processes. In the study, the stages of constructing, analyzing, and interpreting mathematical models within an economic context are interpreted as a factor in enhancing a teacher’s professional excellence. The article proposes a system of problem-based economic tasks that stimulate students’ logical thinking and scientifically substantiates the pedagogical conditions for their implementation in the educational process.